The impact of brillouin pump pre-amplification on multiwavelength brillouin-erbium fiber laser in linear cavity - Mohd Azhan, Mirsa Nurfarhan (2019)
Multiwavelength Brillouin Erbium Fiber Lasers (BEFLs) gain interest in recent decades due to their inherent characteristics such as narrow linewidth, high optical power and single frequency. Generation of multiple wavelengths is realizable through combination of Brillouin and Erbium-Doped Fiber Amplifier (EDFA) gain in the laser cavity. Recent developments of multiwavelength BEFL utilize virtual mirrors in their configuration and most of them amplify the Brillouin pump (BP) once before it oscillates in the laser cavity. Therefore, curiosity now arises as how the number of BP pre-amplification affects the performances of the multiwavelength BEFL. Aspired to answer the curiosity, the impact of BP pre-amplification on the multiwavelength BEFL is studied in this thesis. Comparison with three different schemes of without, single and double BP pre-amplification is carried out for the performance optimization. Experimental results suggest that the scheme with single BP pre-amplification achieves the best performances than the schemes of without and double BP pre-amplification. When the BP wavelength is set at 1550 nm, the scheme of single BP pre-amplification has 8 channels, which is higher than 4 channels for the scheme of double BP pre-amplification and 2 channels for the scheme without BP pre-amplification. For the threshold power meanwhile, the scheme with single BP pre-amplification records the lowest value of 6.8 mW as opposed to 13 mW and 12.7 mW recorded for the scheme of without and double BP pre-amplification respectively. In terms of stability, the scheme with double BP pre-amplification produces the most stable output spectra with 0.39 dB peak fluctuation in comparison to 17.3 dB and 2.44 dB for the scheme of without and single BP pre-amplification respectively. All in all, multiwavelength BEFL with single BP pre-amplification records the best performances with respect to the number of channels and threshold power but, the laser is found to be the most stable when employing double BP pre-amplification technique.